Gene Expression of myosin heavy chain isoforms in pigs of different genetic groups and ages - Ribeiro, André Mauric Frossard (2015)
The objective of this study was to evaluate gene expression pattern of myosin heavy chain isoforms in pigs of three different genetic groups at four ages. 48 castrated males of Piau, Commercial and Crossbred (Piau X Commercial) genetic group, slaughtered at birth, 56, 112 and 156 days. Longissimus dorsi muscle samples were taken for RNA extraction. The expression of MyHC I, MyHC IIA, MyHC IIX and MyHC IIB were analyzed by quantitative PCR (qPCR). Interactions between genetic groups and slaughtered ages to MyHC I, MyHCII A and MyHC IIB relative transcript abundance were observed. The expression of MyHC I was significantly different between birth and 56 days in Piau and Crossbred, mainly in Piau, which showed 81-fold decrease (P < 0.0001). At birth the expression of MyHC I in Piau was nearly 23 and 9.6 times greater than Commercial (P = 0.0028) and Crossbred (P = 0.0258), respectively, explaining the higher proportion of MyHC I transcripts in Piau. The expression of MyHC IIA was significantly higher at birth in comparison to 56 days for all genetic groups, especially in Commercial (P < 0.001, FC=16.04). The expression of MyHC IIA at 56 days in Commercial was 3.76 (P = 0.0346) and 5.4 times lower (P = 0.0082) than Crossbred and Piau. The difference in expression of MyHC I and MyHC IIA across genetic groups at birth can be explained by embryonic development .The expression of MyHC IIB relative to birth, contrary to MyHC I and MyHC IIA, had a significant increase across the ages with highest value at 156 days in Commercial (P < 0.001, FC = 110.22) and Crossbred (P = 0.014, FC=10.49) while in Piau was at 112 days (P = 0.012, FC = 24.34). There was a reversion of proportion of oxidative MyHC (MyHC I and MyHC IIX) to glycolytic MyHC (MyHC IIX and MyHC IIB) in all genetic groups however the rates of this reversion were different. The earlier inflexion in Piau and Crossbred may be due to the difference in partitioning of energy undergoing to protein and/or lipid synthesis, and the respective efficiencies of synthesis. Commercial and Crossbred at 56 days shows higher proportion of oxidative isoforms than Piau (P-value=0.012, P-value=0.023) while at 112 and 156 days Piau shows higher proportion of these isoforms compared to Commercial. The difference of MyHC proportions across genetic groups are caused by difference in expression of oxidative MyHC.